A pair of light signaling factors FHY3 and FAR1 regulates plant immunity by modulating chlorophyll biosynthesis. Issue 1 (24th July 2015) - Wang, Wanqing; Tang, Weijiang; Ma, Tingting; Niu, De; Jin, Jing Bo; Wang, Haiyang; Lin, Rongcheng
Abstract: Light and chloroplast function is known to affect the plant immune response; however, the underlying mechanism remains elusive. We previously demonstrated that two light signaling factors, FAR‐RED ELONGATED HYPOCOTYL 3 (FHY3) and FAR‐RED IMPAIRED RESPONSE 1 (FAR1), regulate chlorophyll biosynthesis and seedling growth via controlling HEMB1 expression in Arabidopsis thaliana . In this study, we reveal that FHY3 and FAR1 are involved in modulating plant immunity. We showed that the fhy3 far1 double null mutant displayed high levels of reactive oxygen species and salicylic acid (SA) and increased resistance to Pseudomonas syringae pathogen infection. Microarray analysis revealed that a large proportion of pathogen‐related genes, particularly genes encoding nucleotide‐binding and leucine‐rich repeat domain resistant proteins, are highly induced in fhy3 far1 . Genetic studies indicated that the defects of fhy3 far1 can be largely rescued by reducing SA signaling or blocking SA accumulation, and by overexpression of HEMB1, which encodes a 5‐aminolevulinic acid dehydratase in the chlorophyll biosynthetic pathway. Furthermore, we found that transgenic plants with reduced expression of HEMB1 exhibit a phenotype similar to fhy3 far1 . Taken together, this study demonstrates an important role of FHY3 and FAR1 in regulating plant immunity, through integrating chlorophyll biosynthesis and the SA signaling pathway. Abstract : This study reveals that two light signaling transcription factors modulate plant immune response through regulating chlorophyll biosynthesis and the salicylic acid biosynthetic and signaling pathways.